On the dose dependence prior and after stimulation with visible light of E' and Al-hole centres in sedimentary quartz: Correlation and mechanisms. (February 2021) - Benzid, Khalif; Timar-Gabor, Alida
Abstract: E′ and Al-hole centres are some of the most common and abundant paramagnetic defects in sedimentary quartz. Here we investigate the dose dependence of these defects before and after exposure to light by electron spin resonance (ESR). Unlike the Al-hole centre, known to have only radiation-induced formation mechanisms, the E′ centre seems to possess a response to gamma dose characterised by predominantly radiation-induced annihilation at lower doses (up to about 1000 Gy) and a predominantly radiation-induced formation at higher doses, at least in the investigated dose range (up to 40 kGy) and samples. We propose these dose response mechanisms to be governed by electron trapping by E′ centre itself and by hole trapping by the oxygen deficiency centre (ODC), that seems to be the main precursor of E' centre. We show that the ESR signals of both defects are linearly correlated during their formation as well as during their dissociation under both irradiation and sunlight exposure. The amount of E′ formed after light exposure was found to follow a saturating exponential behaviour as function of the annihilated Al-hole concentration in respect to dose, saturation being reached for doses of about 1000 Gy, probably due to the exhaustion of ODC population. As such, we propose that the origin of the unbleachable part of the Al-hole signal resides in the availability of oxygen deficiency centres which is also dependent on the accumulated gamma dose. Highlights: Gamma-irradiation leads to E′ centre dissociation as well as its formation in respect to dose. Oxygen deficiency centre (ODC) is the main precursor of E′ centre. Al-hole and E′ centres show a strong correlation under electronic excitations. The electron-hole recombination or the bleaching process occurs at Al-hole/ODC site. The Al-unbleached part is related the ODC concentration in quartz.